2008
DOI: 10.1111/j.1440-0960.2008.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Painful digital infarction in a male smoker treated as Buerger's disease

Abstract: A 40-year-old male smoker presented with a 3-week history of painful digital infarction involving the hands. Histology was unhelpful, showing lichen simplex chronicus. A provisional diagnosis of a vasculitic disease was made. Treatment included aspirin, azathioprine, iloprost, methylprednisolone, nifedipine and prednisolone. After failure of these treatments an alternative clinical diagnosis of Buerger's disease was made. Treatment was to advise the patient of the importance of continuing to abstain from smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[1][2][3] The confusing etiopathogenesis of this disorder often makes it difficult to diagnose and treat. 3 The obstructed vessels with thrombi can be detected in microscopic scans, and thrombotic findings can be revealed in pathological examinations of the affected vessel sites. 4,5 Platelet activation and thrombotic events at affected sites of the vascular system are known to play a crucial role in cardiovascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The confusing etiopathogenesis of this disorder often makes it difficult to diagnose and treat. 3 The obstructed vessels with thrombi can be detected in microscopic scans, and thrombotic findings can be revealed in pathological examinations of the affected vessel sites. 4,5 Platelet activation and thrombotic events at affected sites of the vascular system are known to play a crucial role in cardiovascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally 29 (97%) subjects had smoking history in TAO group and 22 (73%) in control group. TAO is diagnosed and treated with difficulty because of elusive etiology (10]. There is no sufficient knowledge about the other risk factors and predisposing conditions in the literature [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, TAO patients may not benefit from Iloprost without also quitting smoking. [64][65][66] Cigarette smoking activates P-selectin expression by platelets and stimulates the CD40-CD40L pathway. CD40L of platelets interacts with endothelial CD40 and then mediates an array of proinflammatory effects, including the expression of cytokines, chemokines and adhesion molecules.…”
Section: Smoking and Plateletsmentioning
confidence: 99%
“…PGI2 analogs decrease arteriole spasm, endothelial selectin and vWF concentrations and inhibit platelet aggregation. [64][65][66] They also activate fibrinolysis and decrease reactive oxygen species (ROS) production. 119,120 Several clinical trial studies demonstrated that Iloprost administration is more effective than sympathectomy.…”
Section: Taos and Drug Targetsmentioning
confidence: 99%